2021
DOI: 10.9734/ajpas/2020/v10i330248
|View full text |Cite
|
Sign up to set email alerts
|

The Zubair-dagum Distribution

Abstract: This article examines the flexibility of the Zubair-G family of distribution using the Dagum distribution. The proposed distribution is called the Zubair-Dagum distribution. The various mathematical properties of this distribution such as the Quantile function, Moments, Moment generating function, Reliability analysis, Entropy and Order statistics were obtained. The parameter estimates of the proposed distribution were also derived and estimated using the maximum likelihood estimation method. The new distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In contributing to this gap in the literature, Uwaeme and Akpan [22] proposed a new two-parameter distribution called the Remkan distribution. The Remkan distribution is a three-component density of an exponential ( ), gamma (3, ), and gamma (4, )…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contributing to this gap in the literature, Uwaeme and Akpan [22] proposed a new two-parameter distribution called the Remkan distribution. The Remkan distribution is a three-component density of an exponential ( ), gamma (3, ), and gamma (4, )…”
Section: Introductionmentioning
confidence: 99%
“…The authors introduced some of the mathematical properties of the new distribution. They showed that the Remkan distribution exhibits shapes that are not bell-shaped, but positively skewed, unimodal, and right-tailed (Uwaeme and Akpan [22]).…”
Section: Introductionmentioning
confidence: 99%